2017
DOI: 10.1111/cch.12479
|View full text |Cite
|
Sign up to set email alerts
|

Examining the psychological and social impact of relative age in primary school children: a cross‐sectional survey

Abstract: For children with complex difficulties, being relatively young for their school year may be an additional stressor that may undermine mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(61 reference statements)
2
9
0
Order By: Relevance
“…Some studies established relationships between age and happiness in general and based on early trauma and stressful events experienced throughout life. Some studies found no significant difference in the happiness levels between children, adolescents, and adults [ 10 , 76 ]. Another study showed individual happiness determined by age and found a U-shaped relationship between age and happiness [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies established relationships between age and happiness in general and based on early trauma and stressful events experienced throughout life. Some studies found no significant difference in the happiness levels between children, adolescents, and adults [ 10 , 76 ]. Another study showed individual happiness determined by age and found a U-shaped relationship between age and happiness [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was dichotomized, comparing children from the most deprived bottom two decile-based categories with those from the higher 8 categories. We also used the child's relative age in the year group, as this is associated with mental health and SEN in this and other samples; relative maturity correlating with better mental health and educational adjustment (Goodman, Gledhill, & Ford, 2003;Price, Allen, Ukoumunne, Hayes, & Ford, 2017). Relative age was used as a continuous variable with zero being the youngest possible for the year group and one being the eldest.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Children aged 8 in the school setting scored themselves as happier than children aged 5 in the preschool ( d = 0.488; p = 0.007). The age variable has previously not been reported as a significant predictor of the total score [ 13 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Siblings reported slightly increased perceived happiness after the intervention, although the difference was not statistically significant [ 58 ]. Furthermore, the HIFAMS has been used to compare relative differences for children born at different time points during the year [ 59 ]. Children with suspected Attention deficit hyperactivity disorder (ADHD) ( n = 47) have also been reported to have significantly lower HIFAMS scores than their peers (mean difference −1.2, 95% CI = [−0.5, −1.8]; p = 0.001) [ 57 ].…”
Section: Introductionmentioning
confidence: 99%